2014
DOI: 10.1590/1678-7062
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and Doppler ultrasonography on a goat with gangrenous mastitis

Abstract: Communication [Comunicação]Conventional and Doppler ultrasonography on a goat with gangrenous mastitis [Ultrassonografia convencional e Doppler em cabra com mastite gangrenosa]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In a study conducted in goats (19), PI and SPV were increased in animals with clinical mastitis, resulting from an increase in blood flow due to infection-related inflammation. In the present study, PI and SPV were found to be higher in CMT-positive animals, although the difference was statistically insignificant.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a study conducted in goats (19), PI and SPV were increased in animals with clinical mastitis, resulting from an increase in blood flow due to infection-related inflammation. In the present study, PI and SPV were found to be higher in CMT-positive animals, although the difference was statistically insignificant.…”
Section: Discussionmentioning
confidence: 96%
“…Berger et al reported that pulsed wave Doppler ultrasonography can be used to analyze blood flow to udder, sharing the finding that ultrasonographic parameters regarding blood flow to udder increased with milk yield (1). Pulsed wave Doppler ultrasonography is used to measur values such as Time-Averaged Maximum Velocity (TAMV), blood flow volume, Systolic Peak Velocity (SPV) and Resistant Index (RI) in vessels supplying blood to udders (10,17,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding mastitis, many studies have employed the Doppler ultrasonographic examination for the investigation of the infection in cattle [ 53 ], buffaloes [ 54 ], and sheep [ 50 ], thus nowadays the Doppler examination is considered a precise method for the diagnosis of this disease. Santos et al [ 55 ] have indicated that increased PSV and RI in cases of mastitis in goats are probably related to more severe infections. Furthermore, the examination of the supramammary lymph nodes may also provide useful information regarding infection in cows [ 42 ].…”
Section: Ultrasonographymentioning
confidence: 99%
“…This technique allows non-invasive investigation of the cistern and could be useful as a new approach to study udder changes to accommodate milk accumulation during different milking intervals and after milk letdown (Salama et al, 2004). Ultrasonography has been used as a non-invasive method to study the internal structure of the mammary gland in dairy goats (Melo et al, 2012;Díaz et al, 2013;Alejandro et al, 2014;Dar et al, 2014;Fasulkov et al, 2014a,b;Santos et al, 2014Santos et al, , 2015, and cows (Bruckmaier et al, 1994;Ayadi et al, 2003;Bobić et al, 2014;Esselburn et al, 2015;Khoramian et al, 2015) in order to measure the milk storage capacity within the udder. The aim of the present study was to estimate genetic parameters underlying selected udder measurements as detected by ultrasonography.…”
Section: Introductionmentioning
confidence: 99%